Social Entrepreneurship Via Corporate Waqf: A Case of Islamic Chamber of Commerce (ICC) in Malaysia - Wan Norhayate, Wan Daud; Zulhamri, Abdullah; Mohd Rafi, Yaacob (2014)
This case study explore how social entrepreneurship model via Corporate Waqf can be implemented on the context of eradicating urban poverty in Malaysia. This study begins with the introduction of brief background of Islamic Chamber of Commerce (ICC). A background of ICC’s organization structure, vision, mission and its functions are described comprehensively. The study documents the operational characteristics and environment of the social entrepreneurship of ICC. We measure three key characters of social entrepreneurship – innovation, proactiveness, and risk taking on the current practice of organization. We found that ICC is being proactively in achieving their mission. Specifically. ICC can be considered as innovation, proactiveness and risk taking in being efficient financially. The organization focuses on elevating their members’ socio-economic living standard through corporate waqf initiatives. This study implies that social entrepreneurship model via Corporate Waqf has a great potential and can be effectively practice to eradicate urban poverty in the country.